Trends in global and regional incidence and prevalence of hypertensive disordersin pregnancy (1990–2021): an age-period-cohort analysis - Shu Sun; Wangshu Li; Xu Zhang; Aziz ur Rehman Aziz; Na Zhang (Scientific Reports)
Abstract Hypertensive disorders of pregnancy (HDP) are significant global health issues. This study utilized data from the Global Burden of Disease Study 2021 to analyze trends in incidence, prevalence, and Disability-Adjusted Life Years (DALY) associated with HDP across 204 countries from 1990 to 2021. The analysis employed estimated annual percentage changes and an age-period-cohort model, stratifying data by age, year, geographical region, and sociodemographic index (SDI). Statistical analyses and visualizations were conducted using R. Between 1990 and 2021, global HDP incidence rose from 31.33 million to 36.10 million cases (15.24%), while prevalence surged from 6.15 million to 36.10 million cases (487%). Despite the increase in absolute cases, the age-standardized rates for incidence and prevalence exhibited only modest changes, with incidence up by 15.23% and prevalence slightly declining. Regions with high and high-middle SDI showed decreasing trends, whereas middle, low-middle, and low SDI regions faced rising trends. DALYs linked to HDP decreased from 6.96 million in 1990 to 4.94 million in 2021, with significant reductions in high SDI areas. Projections indicate a continued decrease in the global burden of HDP by 2040. The study concludes that continued efforts in prenatal care and health education are vital, particularly in low SDI regions, to mitigate the impact of HDP.